1999
DOI: 10.1111/1467-8624.00080
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attention in the Development of Short‐Term Memory: Age Differences in the Verbal Span of Apprehension

Abstract: In previous studies of memory span, participants have attended to the stimuli while they were presented, and therefore have had the opportunity to use a variety of mnemonic strategies. In the main portion of the present study, participants (first- and fourth-grade children, and adults; 24 per age group) carried out a visual task while hearing lists of spoken digits and received a post-list digit recall cue only occasionally, for some lists. Under these conditions, list information presumably must be extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
132
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 54 publications
15
132
0
2
Order By: Relevance
“…Second, the suggestion that sensory memory decay might have been the limiting factor does not agree with the findings from the short test delays that Cowan et al (1999) used. Cowan et al (1999Cowan et al ( , 2000 found pronounced bow-shaped serial position functions in memory for ignored speech, so sensory memory for even the early serial positions seemed to remain available at the time of list-recall testing.…”
Section: Memory For Ignored Speechmentioning
confidence: 79%
See 4 more Smart Citations
“…Second, the suggestion that sensory memory decay might have been the limiting factor does not agree with the findings from the short test delays that Cowan et al (1999) used. Cowan et al (1999Cowan et al ( , 2000 found pronounced bow-shaped serial position functions in memory for ignored speech, so sensory memory for even the early serial positions seemed to remain available at the time of list-recall testing.…”
Section: Memory For Ignored Speechmentioning
confidence: 79%
“…If the focus of attention could repeatedly access that record, it would be difficult to explain the limit to about 4 items recalled from unattended lists (Cowan, 2001;Cowan et al, 1999). Also, some procedures include a cue to examine only one object within the memory record of an array (e.g., Luck & Vogel, 1997) or list (Cowan, Johnson, & Saults, in press), yet a similar capacity limit of about 4 items is obtained.…”
Section: Assumption 3: Single Iteration Of Retrievalmentioning
confidence: 99%
See 3 more Smart Citations